2018
DOI: 10.1021/acs.jpcc.8b04063
|View full text |Cite
|
Sign up to set email alerts
|

Guided Growth of Horizontal ZnS Nanowires on Flat and Faceted Sapphire Surfaces

Abstract: The surface-guided growth of horizontal nanowires (NWs) allows assembly and alignment of the NWs on the substrate during the synthesis, thus eliminating the need for additional processes after growth. One of the major advantages of guided growth over postgrowth assembly is the control on the NWs direction, crystallographic orientation, and position. In this study, we use the guided growth approach to synthesize high-quality, single-crystal, aligned horizontal ZnS NWs on flat and faceted sapphire surfaces, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 69 publications
6
20
0
Order By: Relevance
“…This indicates that although the preferred growth direction is along [ 101] Al2O3 , this preference is not as strong as along the opposite [1 01] Al2O3 direction. The nearly ±40° deviation from [ 101] Al2O3 is consistent with the {20 } Al2O3 directions that were found to be preferred by other Wurtzite-structure nanowires like ZnS 19 , ZnSe 17 and CdSe 20 . This means that although the catalyst determines the polarity of the nanowires, the interaction with the surface does still have a significant effect, and there could be a competition between surface-determined and growth direction-determined polarity.…”
Section: Resultssupporting
confidence: 82%
“…This indicates that although the preferred growth direction is along [ 101] Al2O3 , this preference is not as strong as along the opposite [1 01] Al2O3 direction. The nearly ±40° deviation from [ 101] Al2O3 is consistent with the {20 } Al2O3 directions that were found to be preferred by other Wurtzite-structure nanowires like ZnS 19 , ZnSe 17 and CdSe 20 . This means that although the catalyst determines the polarity of the nanowires, the interaction with the surface does still have a significant effect, and there could be a competition between surface-determined and growth direction-determined polarity.…”
Section: Resultssupporting
confidence: 82%
“…The thickness of each modulation (as it appears in the image) is around 2 nm. Similar kinds of structural patterned HRTEM images have been observed in the past, showing mixed zinc blende and wurtzite phases and appearance of stacking faults [11,17,[39][40][41][42]. In particular, Liang et al reported the vertically oriented growth of ZnS NWs assisted by Au, Ag and Ga catalysts [39,43] and emphasized the crystal phase dependence upon NW diameter.…”
Section: Structural Analysissupporting
confidence: 65%
“…These NWs grew along the same 6 isoperiodic m <10 10 > directions of the sapphire but had the wurtzite crystal structure with an axial growth direction of m ½ 1100 as shown in Fig. 3 A-C. Also here, previous study (27) presents full details about the crystal phases, epitaxial relations, and crystallographic orientations for ZnS NWs grown under the exact same conditions. ZnS NWs were also grown on faceted annealed M-plane and miscut C-plane sapphire substrates, presenting graphoepitaxial growth along the nanogrooves and nanosteps (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 87%
“…Following these pioneering works on surface-guided growth of NWs, Joselevich and coworkers (9) generalized this approach from epitaxial to graphoepitaxial growth, including millimeter-long GaN NWs with controlled orientations on different planes of sapphire. Such controlled guided growth of planar NWs was then extended beyond GaN (9,20,21) to other semiconductor materials, such as ZnO (4,22), ZnSe (23), ZnTe (24), CdSe (25), CdS (26), and ZnS (27). Core-shell NW and nanowall heterostructures were also demonstrated and integrated into efficient photodetectors and photovoltaic cells (28,29).…”
mentioning
confidence: 99%